The risk of osteoporosis in patients with asthma. Issue 1 (1st January 2020) - Kumarathas, Indumathi; Harsløf, Torben; Andersen, Charlotte Uggerhøj; Langdahl, Bente; Hilberg, Ole; Bjermer, Leif; Løkke, Anders
ABSTRACT: It is well-known that use of continuous systemic corticosteroids (SG) affects bone metabolism, bone mineral density (BMD), and ultimately increases the risk of osteoporosis. In patients with asthma, on the other hand, the effects of long-term high-dose inhaled corticosteroids (ICS) on BMD and risk of osteoporotic fractures is controversial. The reasons for this inconsistency could be explained by the fact that only few long-term studies investigating the effect of ICS in patients with asthma exist. The studies are characterized by different study designs and duration of ICS exposure, small study populations, and differences between the used ICS. The aim of this article is to unravel which factors, if any, that contribute to an increased risk of osteoporosis in patients with asthma and to summarize the evidence regarding adverse effects of ICS on bone metabolism, BMD and osteoporotic fractures in patients with asthma.